The effects of the herbicides terbuthylazine and metazachlor at environmental concentration on the burrowing behaviour of red swamp crayfish - Guo, Wei; Weiperth, András; Hossain, Md Shakhawate; Kubec, Jan; Grabicová, Kateřina; Ložek, Filip; Veselý, Lukáš; Bláha, Martin; Buřič, Miloš; Kouba, Antonín; Velíšek, Josef (Chemosphere, 2021)
Despite their low concentrations in many aquatic environments, evidence exists to suggest that herbicides do affect non-target organisms. Given that burrowing is a primary life-history trait in crayfish, herbicides could potentially have serious negative effects on these ecologically important freshwater macroinvertebrates. In this study, we exposed the red swamp crayfish Procambarus clarkii to terbuthylazine (a triazine) and metazachlor (a chloroacetanilide) at an environmental concentration of 2.0 μg/L for 28 days, and then observed their burrowing behaviour for two days. The metazachlor-exposed males excavated a greater number of burrows than the other tested groups, with comparable depths and volumes relative to individual specimen weight. The relative depth and volume of female burrows were identical in all groups. The natural habit of female crayfish of constructing deeper burrows than males was marginally significant in the control and META groups but was not significant for relative volume. The hypothesized adverse effects of chronic exposure to real environmental concentrations of herbicides were not documented in terms of either relative depth or volume. However, the increased number of burrows in metazachlor-exposed animals may mean that this invasive species will cause greater damage to embankments and river banks. The mechanisms behind these effects require closer study.
Keywords: triaziny; Terbuthylazine; Weed control; mužské pohlaví; acetamidy; Triazines; Acetamides; Procambarus clarkii; Metazachlor; herbicidy; ženské pohlaví; Astacoidea; zvířata; severní raci; Drought; Herbicides; Female; Male; Macroinvertebrate; Animals